Dynamics of insect communities across a unique network of hydrologically altered riparian habitats in central China. Issue 8 (28th August 2022) - Butler, Orpheus M.; Ye, Chen; Zhang, Quanfa
Abstract: The establishment of hydroelectric dams can lead to major changes in hydrology for habitats within the reservoir drawdown zones. The Three Gorges Dam (TGD) in China is the world's largest hydroelectric facility, with a reservoir covering 1080 km 2 and a drawdown zone covering 350 km 2 . Since the TGD's establishment in 2008, the formerly terrestrial habitats within the dam's drawdown zone have effectively been converted to riparian habitats. A strong understanding of ecological dynamics in these novel habitats is critical to their ongoing management. Given the major contribution of insects to ecosystem function and biodiversity, we surveyed riparian insect communities semi‐annually from 2011 to 2018 across a 600‐km network of 18 sites in the TGD's drawdown zone. During this period, the total abundance of insects increased 4.4‐fold, and the composition of insect communities shifted significantly, with Diptera increasingly dominant in later years. Insect abundance trajectories were coupled with concomitant changes in local climate and soil chemistry, which have in turn been brought on by the novel hydrological regime in the drawdown zone. Revegetation efforts had limited impacts on riparian insect abundances. Overall, riparian insect communities have undergone marked shifts since the TGD started operating. We cannot explicitly attribute these effects to the TGD's establishment, but our results indicate that they might have been shaped by—or are at least coupled with—the profound changes in hydrological conditions associated with the TGD's establishment.